2020
DOI: 10.1111/jocd.13464
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double‐blind vehicle controlled study of the effects of topical acetyl zingerone on photoaging

Abstract: The trillion-dollar wellness industry is made up in large part of beauty and antiaging products, and continues to grow. 1-3 Currently, one of the main antiaging therapies involves the use of retinoids to treat wrinkles and pigmentation due to their ability to ameliorate hyperpigmentation and upregulate collagen. 4,5 Despite these therapeutic benefits, retinoids often have unwanted side effects such as scaling, itching, and redness. 6 The high rates of the use of retinoids and resulting side effects experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…The obtained results show that the addition of ginger to the formula enhances the effect of AA by three orders of magnitude compared to other tested combinations. Moreover, previous studies performed with ginger formulations demonstrated its efficacy in preventing cell damage and signs of cutaneous photoaging [24,25].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The obtained results show that the addition of ginger to the formula enhances the effect of AA by three orders of magnitude compared to other tested combinations. Moreover, previous studies performed with ginger formulations demonstrated its efficacy in preventing cell damage and signs of cutaneous photoaging [24,25].…”
Section: Discussionmentioning
confidence: 92%
“…Both glutathione and ginger showed the best results for increasing the antioxidant effect of vitamin C + E (control). In light of these results, ginger was chosen as the best enhancer ahead of glutathione because of its complementary properties [24,25].…”
Section: In Tubo Studymentioning
confidence: 99%
“…Previous studies have identified MMPs as playing an important role in skin aging through the propagation of collagen breakdown 7 . More recently, a double‐blind randomized controlled study by Dhaliwal et al., 8 demonstrated a significant decrease in average wrinkle severity, total wrinkle volume, pigment intensity, and redness intensity in a group of patients who used 1% topical acetyl zingerone on the face twice daily for 8 weeks compared to a control group who applied a placebo. Lee et al., 9 examined the effects of zingerone on the properties of keratinocyte stems irradiated with UVB.…”
Section: Dermatologic Applicationsmentioning
confidence: 99%
“…This plants were used in cooking long time ago and also as a spice and traditional treatment like vomiting, nausea, pain, arthritis, indigestion, gastro reflux. 3 Moreover, many several uses of ginger tablet was useful in treating, managing, or preventing many diseases like cardiovascular disease, diabetes, 4 obesity, 6 respiratory disease, 5 nausea and vomiting induced by chemotherapy 7 and in neurodegenerative diseases; it also in-holds some of the biological properties like antimicrobial, 8 anti-inflammation, 9 antioxidant, 10 anticancer, 11 and wound healing properties. 12 In previous researches, there is different active contains of herbal medicinal plants showed different effective on poultry performance.…”
Section: Introductionmentioning
confidence: 99%